2012
DOI: 10.1371/journal.pone.0046793
|View full text |Cite
|
Sign up to set email alerts
|

Human Exposure Pathways of Heavy Metals in a Lead-Zinc Mining Area, Jiangsu Province, China

Abstract: Heavy metal pollution is becoming a serious issue in developing countries such as China, and the public is increasingly aware of its adverse health impacts in recent years. We assessed the potential health risks in a lead-zinc mining area and attempted to identify the key exposure pathways. We evaluated the spatial distributions of personal exposure using indigenous exposure factors and field monitoring results of water, soil, food, and indoor and outdoor air samples. The risks posed by 10 metals and the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(119 citation statements)
references
References 42 publications
9
104
6
Order By: Relevance
“…Some subjects in FD showed even higher levels of Cd and Pb, with the maxima estimated at 1.94 and 38 mg/kg, respectively. The average levels of hair Pb, Cd, Cu and Zn in the study area were lower than the levels in the scalp hair of adults from S. Domingos mine, Portugal [60], but higher than those recorded in a lead-zinc mining area from China [9]. Interestingly, the Zn concentration in hair of a non-exposed population was higher than that of subjects living near the Dabaoshan mine, which might be due to the higher concentration of toxic metals like Cd and Pb in the vicinity, which can interact with Zn and replace it in the heme enzymes and metallothioneins [61].…”
Section: Resultscontrasting
confidence: 66%
“…Some subjects in FD showed even higher levels of Cd and Pb, with the maxima estimated at 1.94 and 38 mg/kg, respectively. The average levels of hair Pb, Cd, Cu and Zn in the study area were lower than the levels in the scalp hair of adults from S. Domingos mine, Portugal [60], but higher than those recorded in a lead-zinc mining area from China [9]. Interestingly, the Zn concentration in hair of a non-exposed population was higher than that of subjects living near the Dabaoshan mine, which might be due to the higher concentration of toxic metals like Cd and Pb in the vicinity, which can interact with Zn and replace it in the heme enzymes and metallothioneins [61].…”
Section: Resultscontrasting
confidence: 66%
“…For example, Cabrera et al [53] found that the sensitivity to health risk of pesticide will affect the farm workers’ behavior. In many exposure assessment studies [54], [55], researchers have found that individuals’ behaviors would result in the difference of actual risk. Huang et al [56] and Marchwinska et al [57] believed improving access to education and better risk communication to increase sensitivity will reduce high-risk behaviors and strengthen local governments’ credibility for risk reduction, control and management.…”
Section: Discussionmentioning
confidence: 99%
“…The stratigraphic succession (Fig. 2) in the El-Minya area is represented by Tertiary and Quaternary sedimentary rocks (Said, 1981). The main aquifer in the study area is represented by Pleistocene sediments which are composed of sand and gravel of different sizes with some clay intercalation (Sadek, 2001).…”
Section: Locationmentioning
confidence: 99%
“…So, quantifying human risk (carcinogenic and non-carcinogenic risks) of Cd and Pb to children and adults is important. The hazard quotient (HQ) is extensively used to characterize the carcinogenic and non-carcinogenic health effects of toxic metals by comparison of their exposure effects to a reference dose (Rf D) (Qu et al, 2012). This was documented in several studies by taking into consideration exposure scenarios of metal intake through contaminated water (Muhammad et Shah et al, 2012;Dou and Li, 2012).…”
Section: Introductionmentioning
confidence: 99%